Образ Петра I в повести А. Ремизова «Крестовые сестры» [The Image of Peter the Great in Alexei Remizov’s Short Novel “The Sisters of the Cross”] - Dotsenko, Sergei (Slavica Revalensia, 2017)
This article explains the ambivalence of the image of Peter the Great, and his policy of Russia’s Europeanization. According to Alexei Remizov, Peter’s projects were mad and utopic, just like those of Ugryum-Burcheev, a character of Mikhail Saltykov-Shchedrin’s The History of a Town (1870), yet at the same time for Remizov they were essentially Russian in spirit.